The characteristics and factors associated with omitted nursing care in the intensive care unit: A cross-sectional study. (April 2023) - Vincelette, Christian; D'Aragon, Frédérick; Stevens, Louis-Mathieu; Rochefort, Christian M.
Abstract: Introduction: Prior research showed that work environment features in acute care settings influence nurses' capacity to provide care and impacts patient outcomes (e.g., falls). However, little is known about this phenomenon in the intensive care unit. The objectives of this study were to describe the characteristics of omitted nursing care, and to examine the associations between work environment features, omitted nursing care and nurse-reported outcomes in the intensive care unit. Methods: An electronic cross-sectional correlational study was conducted in the province of Quebec, Canada. Over September 2021, nurses were asked to complete the Healthy Work Environment Assessment Tool (HWEAT), the Intensive Care Unit Omitted Nursing Care instrument (ICU-ONC) and to report their perceptions of nurse-reported outcomes (e.g., quality of care). The associations between these variables were estimated using multivariable cluster-robust regression models, adjusted for nurse and hospital characteristics. Results: A total of 493 nurses from 42 distinct hospitals participated to this study. On average, nurses felt that their work environment was acceptable, and that the quality and safety of patient care was good. Basic care activities (e.g., mobilisation) were most frequently reported as omitted as opposed to those related to surveillance and medical interventions. In multivariable analyses, higher work environment scores were associated with reduced omitted nursing care scores ( p < 0.001) and better ratings for nurse-reported outcomes ( p < 0.001). Also, higher omitted nursing care scores were associated with more negative perceptions about the quality and safety of care ( p < 0.001). Conclusion: Our study portrays the characteristics and some factors associated with omitted nursing care in the intensive care unit. Further research should determine whether intensive care nurses' reports of organisational features and omitted nursing care are associated with objectively captured patient outcomes.